2016
DOI: 10.4236/ajps.2016.712155
|View full text |Cite
|
Sign up to set email alerts
|

Review of Studies on the Last Enzymes in Bacteriochlorophyll (<i>Bchl</i>) and Chlorophyll (<i>Chl</i>) Biosynthesis

Abstract: This paper summarizes the information available online related to mechanisms of Chlorophyll and Bacteriochlorophyll biosynthesis, emphasizing four enzymes in its last steps. The biosynthesis of Chlorophyll (Chl)/Bacteriochlorophyll (Bchl) is essential for the occurrence of photosynthesis. Four enzymes catalyze parts of the last chemical reactions steps to biosynthesize Bchl/Chl; they are: The Light-Dependent Protochlorophyllide (Pchlide) Oxidoreductase (LPOR: EC 1.3.1.33), the Light-Independent Pchlide oxidore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Further analysis suggested that an electronic effect of the substituent on the benzylamine moiety had little impact on herbicidal activity. For example, the 3-methylbenzylamine derivative (16) showed activity comparable with that of fluorinated benzylamine derivatives (3,4,7). It seems that the herbicidal activity of the derivatives was strongly affected by a steric effect of the substituents on the benzylamine moiety.…”
Section: Herbicidal Activity In Petri Dish Test 321 Effect Of Substituents (R 1 ) On the Benzylamine Moietymentioning
confidence: 99%
See 2 more Smart Citations
“…Further analysis suggested that an electronic effect of the substituent on the benzylamine moiety had little impact on herbicidal activity. For example, the 3-methylbenzylamine derivative (16) showed activity comparable with that of fluorinated benzylamine derivatives (3,4,7). It seems that the herbicidal activity of the derivatives was strongly affected by a steric effect of the substituents on the benzylamine moiety.…”
Section: Herbicidal Activity In Petri Dish Test 321 Effect Of Substituents (R 1 ) On the Benzylamine Moietymentioning
confidence: 99%
“…Bleaching herbicides usually have low toxicity to mammals and have attracted increasing interest from chemists. Protoporphyrinogen IX oxidase (PPO), the last enzyme common to both chlorophyll and heme biosynthesis, is a target of Protox herbicides 3 . Diphenyl ether (nitrofen), oxadiazolinone (oxadiazon) and tetrahydrophthalimide (chlorophthalim) are three classes of PPO inhibitors developed in the 1960s to 1980s, and many other non‐classical Protox chemistries have been introduced since 4–7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photosynthesis takes place with the help of the tetrapyrrolic light absorbing pigment molecules bacteriochlorophylls (BChls) and chlorophylls (Chls) in anoxygenic and oxygenic phototrophs respectively (Chen et al 2010;Nascimento et al 2016). The light-dependent reaction takes place in photosynthetic membranes and begins with photon absorption by pigment molecules associated with antennae proteins, followed by excitation energy transfer to the reaction centres (RC).…”
Section: Introductionmentioning
confidence: 99%